2004
DOI: 10.1002/tcr.10072
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic studies of the DSP toxin skeleton

Abstract: Marine toxins have drawn wide interest because their economical impact and disastrous effect upon the shellfish industry and public health in many parts of the world. One of the most interesting group of substances of marine toxins, from structural and pharmacological points of view are polyether compounds, which generally present a great diversity in size and potent biological activities. The subject of this work was about to biosynthesis of okadaic acid skeleton as leader as DSP toxins. Its biosynthesis attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
0
17
0
1
Order By: Relevance
“…Several precursor incorporation studies have also indicated that the PKS pathway participates in DSP toxin biosynthesis [137,138,139,140,141]. Glycolate from photorespiration is a deemed precursor of OA synthesis and side chains of DTX-5 (side chain c and d of R 5 in Figure 1).…”
Section: Putative Mechanism Of Dsp Toxin Productionmentioning
confidence: 99%
“…Several precursor incorporation studies have also indicated that the PKS pathway participates in DSP toxin biosynthesis [137,138,139,140,141]. Glycolate from photorespiration is a deemed precursor of OA synthesis and side chains of DTX-5 (side chain c and d of R 5 in Figure 1).…”
Section: Putative Mechanism Of Dsp Toxin Productionmentioning
confidence: 99%
“…Unfortunately, radiolabeled feeding studies have proven to be quite difficult since Prorocentrum and Dinophysis are very selective genera that undergo autotrophic and heterotrophic metabolism (Izumikawa et al, 2000;Daranas et al, 2004). Daranas and colleagues suggested (2004) that the carbon skeleton of OA is synthesized by an unusual route regarding the direct condensation reactions (acetate, proprionate, or butyrate units) associated with polyethers of terrestrial origin.…”
Section: Okadaic Acidmentioning
confidence: 99%
“…Daranas and colleagues suggested (2004) that the carbon skeleton of OA is synthesized by an unusual route regarding the direct condensation reactions (acetate, proprionate, or butyrate units) associated with polyethers of terrestrial origin. Those authors believed that the parent compound is assembled from a polyketide chain, with glycolate as a starter unit and subsequent additions of acetate (Daranas et al, 2004). The involvement of the tricarboxylic acid cycle in incorporating polyketide fragments into a polyether backbone is unusual and is characteristic of the biosynthesis of dinoflagellate toxins (Shimizu, 1993).…”
Section: Okadaic Acidmentioning
confidence: 99%
“…Among these, the antibody-based immunoassay is attractive, because it is accurate, sensitive, easily performed, and portable. During the development of this immunoassay, extensive studies focused on preparing antibodies with high specificity for ciguatoxin, and recently a sandwich enzymelinked immunosorbent assay using high affinity antibodies specific to both ends of CTX3C was established that can detect CTX3C down to the parts per billion level without cross-reactivity against other related marine toxins (14,15), including brevetoxin A (17), brevetoxin B (18), okadaic acid (19), and maitotoxin (5).…”
mentioning
confidence: 99%
“…Moreover, many marine toxins have polyether structures. These toxins include maitotoxin (5) and gambierol, which also cause ciguatera (5), brevetoxin, which causes neurotoxic shellfish poisoning (17,18), dinophysistoxins, which cause diarrheic shellfish poisoning (19), palytoxin (20), and yessotoxin (21). Therefore, research focused on antibodies that can recognize polyether compounds may produce a more effective antibody-based immunoassay based on well understood mechanisms.…”
mentioning
confidence: 99%